Intensifying neighbouring tree competition suppresses tree growth at the eastern Tibetan tree line - Lyu, Lixin; Büntgen, Ulf; Li, Mai‐He; Yu, Kailiang; Palosse, Audrey; Zhang, Qi‐Bin; Cherubini, Paolo (Functional ecology, 2025)
Although neighbourhood interactions are important for the establishment and survival of tree line trees, it remains poorly understood how they affect growth rates under changing climatic conditions. Here, we combine census data and dendrochronological measurements from 18 tree line plots between 4300 and 4520 m asl on the eastern Tibetan Plateau to develop a retrospective Neighbourhood Index. We then investigate whether tree interaction is facilitative or competitive and whether it changes over time. Our results show that competition for water not only dominates neighbourhood interactions on the eastern Tibetan Plateau, but also increased significantly from 1960 to 2009 (p < 0.001). Contrary to the common belief of facilitative neighbourhood interactions at high elevation, we demonstrate that competition among mature trees is common in tree line ecotones of the eastern Tibetan Plateau, and likely to increase under projected global warming. Read the free Plain Language Summary for this article on the Journal blog. Read the free Plain Language Summary for this article on the Journal blog.